A cobrança de AIH em hospitais que integram a rede de atendimento SUS do estado de Minas Gerais: influência dos procedimentos especiais no valor médio faturado - Isabela Gonçalves Barros de Andrade (2020)
Introduction: One of the remuneration forms for SUS health actions and services occurs in the form of production based on the SUS / SIGTAP unified table. Regardless of the actual costs incurred with patients, the amount passed on by SUS to hospitals follows values defined in the single table per main procedure, plus secondary procedures, special procedures and also increments to the table, which are included in the Hospitalization Authorization (AIH). Special procedures add value to the main procedure and may be underutilized for different reasons. Therefore, the broad knowledge on the part of the billing / medical accounts sector, medical staff, auditors and hospital managers about what special procedures are and how they can be billed can contribute, not only to boost the institution's billing, but also to enhance invoicing, as well as to qualify the information for the right recording of the procedures done in hospitals, which enables better managing performance and management tools for the institutions. Objective: To identify the influence of special procedures on the average AIH value of selected hospitals and possible hypotheses for the differences identified, with a view to improving the billing function. Methodology: This is a cross-sectional study that uses a blending of both quantitative and qualitative methods. It was conducted with records of hospital production that took place between the months of January 2018 to December 2018, in hospitals linked to the SUS of the state hospital care network of Minas Gerais. The study used the database of the Hospital Information System of the Unified Health System (SIH / SUS), which is fed by the Hospitalization Authorization (AIH), the National Register of Health Facilities and the Table Management System of Procedures, Medicines and OPM of SUS / SIGTAP. Description and data analysis: The results showed that if we compare the production of AIH from different institutions, it is common for AIH to exist with the same main procedures and different average values being billed. This study made possible to reach the proposed goal of identifying the influence of special procedures on the average AIH, due to the assessmento of the diversity of types and quantity of billed prodecures for the same main procedure. It was observed that the hospitalization for the treatment of a specific disease in a hospital may present in its AIH different types and quantities of special aggregated procedures, when compared to another hospital, even though it has equal availability of technological resources and a similar morbidity profile. The difference in the average AIH values billed for the same main procedure can be attributed to different types and quantities of special aggregated procedures Final considerations: It is concluded that the hospitalization destined to the treatment of a specific disease in a hospital may present, in its AIH, different types and quantities of special aggregated procedures, when compared to another hospital, even if it has the same availability of resources technological characteristics and a similar morbidity profile and this difference was attributed to the difference in the mean value. The causes suggested for this finding can be attributed by the overuse of special procedures, failure to record medical records, weakness in the billing sector and in the AIH supervision process. It is expected that this study reflections may contribute to the SUS procedures charging, the improvement of assistance and the planning of public health policies.